2014
DOI: 10.1007/s10114-014-2804-5
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of frames

Abstract: In this paper, we give some sufficient conditions under which perturbations preserve Hilbert frames and near-Riesz bases. Similar results are also extended to frame sequences, Riesz sequences and Schauder frames. It is worth mentioning that some of our perturbation conditions are quite different from those used in the previous literatures on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Moreover, he showed that in the case when we lose the assumption q < m Φ , the sequence Ψ is not a frame for the whole space . Hence, in the next two results, inspired by Chen et al, 12 we formulate similar results as above for quadratically close sequences Φ and Ψ whenever Φ is a frame for  and we have m Φ ≤q. Particularly, Example 4.7 below shows that these investigations expand our results to the sequences which do not satisfy the Paley and Wiener perturbation condition.…”
Section: The Perturbation Effect On the Dualsmentioning
confidence: 60%
See 2 more Smart Citations
“…Moreover, he showed that in the case when we lose the assumption q < m Φ , the sequence Ψ is not a frame for the whole space . Hence, in the next two results, inspired by Chen et al, 12 we formulate similar results as above for quadratically close sequences Φ and Ψ whenever Φ is a frame for  and we have m Φ ≤q. Particularly, Example 4.7 below shows that these investigations expand our results to the sequences which do not satisfy the Paley and Wiener perturbation condition.…”
Section: The Perturbation Effect On the Dualsmentioning
confidence: 60%
“…We first study some properties of (canonical) approximately dual frames which have not been touched so far. Second, we show that if we do a sufficiently small perturbation of a frame in the sense of Chen et al and Christensen, 12,13 then their specific approximately dual frames are close to each other. In contrast to the work, 7 we consider the problem in a much more general setting.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…By assumptions, we have W g j ≤ λ g j , T g j ≤ λ g j , j ∈ I. Therefore, [ [11], Theorem 2.14] leads to the desired result.…”
Section: Frame Representation Of the Form {Amentioning
confidence: 87%
“…Alternative norm-perturbation conditions are formulated in [6]; however, they need that we have access to information about a dual frame, which is not the case in the current paper. Note also that a number of classical results about norm-perturbation (typically for orthonormal sequences) are collected in [17].…”
Section: Introductionmentioning
confidence: 98%